HUBUNGAN PENGETAHUAN DENGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI DI SMK NEGERI MOTONGKAD KABUPATEN BOLAANG MONGONDOW TIMUR TAHUN 2024 - Miranda Kilapong (STIKES Columbia Asia Medan, 2024)
Personal hygiene is a personal health effort to maintain and improve one's own cleanliness and health for the sake of well-being. The aim of this research was to determine whether there was a relationship between knowledge and personal hygiene behavior during menstruation in young women at Motongkad State Vocational School. This research method uses a quantitative type of research with a cross-sectional approach. The population was 93 f 2022 emale students and the sample was 76 respondents, with data analysis using SPSS version. Results: There was a relationship between knowledge and personal hygiene behavior during menstruation among young women at Motongkad State Vocational School, where the chi-square test results found a value of ρ = 0.014. It is hoped that future researchers will be able to develop research by determining other variables such as motivation, role of the north and so on which are related to the behavior of young women in reproductive organ hygiene by expanding the scope of research to get even better results.